AMATEUR ASTRONOMY MOVEMENT IN SLOVAKIA - Kudzej, I.; Dubovsky, P. A. (Одеські астрономічні публікації, 2007)
We present brief history of astronom ical education in Slovakia. The actual state of public observatories network is described as well. We also give an example of educational project supported by state agency "Slovak Research and Development Agency".